2020
DOI: 10.1002/pei3.10028
|View full text |Cite
|
Sign up to set email alerts
|

Tissue ionome response to rhizosphere pH and aluminum in tea plants (Camellia sinensis L.), a species adapted to acidic soils

Abstract: Acidic soils account for approximately 50% of the world's potentially arable lands but significantly limit crop production (Kochian, Hoekenga, & Piñeros, 2004). Many crops grow poorly in acid soils because of acid soil syndrome, which consists of multiple stress factors, including phytotoxicity to excess ions such as aluminum (Al 3+), protons (H +), and manganese (Mn 2+), and/or deficiencies of essential minerals such as calcium (Ca), magnesium (Mg), and phosphorus (P) (Kochian et al., 2004). In particular, Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…It has long been known that tea plants can accumulate and tolerate higher concentrations of Al compared to many other plant species [ 12 , 17 , 55 ], and that this characteristic is determined in part by large scale transcriptional changes in response to Al exposure, which include genes involved in Al transport and sequestration, biosynthesis and secretion of organic acids, and modification to the cell wall [ 12 , 13 ]. It is also well known that metal responses are interactive and typically affect other metals, such that changes in the availability and plant accumulation of one metal, such as Al, typically alters the behavior of other metals and mineral nutrients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has long been known that tea plants can accumulate and tolerate higher concentrations of Al compared to many other plant species [ 12 , 17 , 55 ], and that this characteristic is determined in part by large scale transcriptional changes in response to Al exposure, which include genes involved in Al transport and sequestration, biosynthesis and secretion of organic acids, and modification to the cell wall [ 12 , 13 ]. It is also well known that metal responses are interactive and typically affect other metals, such that changes in the availability and plant accumulation of one metal, such as Al, typically alters the behavior of other metals and mineral nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…These indirect effects of Al and H + toxicity provide further plant stress, by evoking subsequent oxidative stresses and triggering cell death [ 8 , 11 ]. While most major crops display significant sensitivity to acidic soils, tea plants can grow normally on most acidic soils containing higher concentrations of Al, without any obvious rhizotoxicity symptoms [ 4 , 12 , 13 ]. So far, at least two broad resistance mechanisms involving external or internal detoxification have been proposed to explain most plant adaptive responses to Al toxicity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrification will also lead to soil acidification. The proper pH for tea growth is about 4.2 [14], and, when the pH is less than 3.8, or higher than 5.0, it is not conducive for tea tree growth. NH 4 + -based fertilizers, such as ammonium bicarbonate and urea, can help prevent rapid nitrification, and improve the nitrogen use efficiency and yield of tea [15].…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of Al 3+ , the original root was hardly growing further and almost no new root appeared in the existing root, and the cell differentiation in the root meristem was decreased rapidly, leading to the root stopping growing. Thus, Al is a beneficial macroelement for tea plants, , and a study even indicated that Al is an essential element for tea plants . The concentration of Al suitable for the growth of tea plant roots can be as high as ≥2 mM. ,, However, the root length of Arabidopsis thaliana was inhibited in the presence of 20 μM Al 3+ .…”
Section: Introductionmentioning
confidence: 99%